Engineered 2D smart nanomaterials and nanocomposites: Advanced frontiers in heavy metal ion detection for water purification - Teotia, Shikha; Verma, Damini; Toshani; Ting, Koo Pey; Kumari, Vanshika; Ahmed, Minhaz Uddin; Das Mukherjee, Maumita (Journal of environmental chemical engineering, 2025)
Heavy metal ions (HMIs), which exist naturally, pose a significant concern to the environment and human health due to their propensity to bioaccumulate, persistence, and toxicity. Industrial emissions, e-waste, urbanization, agriculture, and mining have all contributed to the rapid growth of HMIs contamination due to extensive industrial expansion and technology, which poses a major threat to public health and ecosystems. Consequently, the fabrication of detection techniques for monitoring these HMIs is essential. Recent advances in material science have given this subject renowned interest and sparked the development of distinct nano sensors with a diverse sensor types and applications. The development of highly reliable, specific, and sensitive electrochemical detection techniques based on nanomaterials is crucial to address this growing problem and enable the quick identification of HMIs contamination. Two-dimensional (2D) nanomaterials stand out among them as attractive building blocks for sensors because of their distinct optical, electrical, chemical, and physical characteristics. Because of the nanoscale electrode surface design that results in quick electrode kinetics, active large surface area, conductivity, and enhanced catalytic activity, the resulting electrodes have several benefits and function better. Furthermore, unlike the previous reviews that focused primarily on a particular type nanomaterial-based electrochemical sensors, this work highlights recent advances in electrochemical, optical and piezoelectric platforms for various 2-D materials including graphene, MXene, layered double hydroxides (LDHs), transition metal chalcogenides (TMCs) and other 2-D materials for HMIs detection in real water. Finally, the review outlines current challenges, and research gaps and proposes future directions for optimizing 2D nanomaterial-based sensors for practical water monitoring applications. [Display omitted] •Heavy metal ions persist, bioaccumulate and threaten ecosystems and human health.•Advances in electrochemical, optical and piezoelectric sensors are reviewed.•Graphene, MXenes, LDHs and TMCs explored for HMI detection in real water.•Nanoscale design improves surface area, conductivity and catalytic activity.•Review maps challenges, gaps and advances toward real-world 2D sensor applications.